Strategic planning of proteins in ionic liquids: future solvents for the enhanced stability of proteins against multiple stresses. Issue 42 (17th October 2019) - Kumar, Awanish; Bhakuni, Kavya; Venkatesu, Pannuru
Abstract : Ionic liquids (ILs) represent as solvents or co-solvents for protein stabilization and refolding. Thus, ILs are replacement to toxic organic solvents in chemical, biotechnology and biomedical applications. Abstract : Ionic liquids (ILs) present a vast number of solvents capable of replacing toxic organic solvents in chemical, biotechnology and biomedical applications. ILs are inexpensive and environmentally friendly as the materials can be recycled conveniently. Chemists use a variety of cation and anion combinations to produce an IL that fits the requirements of the sustainable future through the pursuit of greener chemical processes. As such, the development of various types of ILs has been recognized as the emergence of environmentally friendly solvents to attain enhanced protein stability in vitro . The literature survey reveals that there exist a large number of scholarly articles as well as elegant reviews on protein stability in ILs. Biomolecules have adapted to antagonistic environmental stresses that normally denature proteins, and the mechanism of adaptation that protects the cellular components against denaturation involves the intracellular concentration of co-solvents. In this regard, recent experimental results distinctly demonstrated that ILs are stabilizing proteins against denaturing stresses, and their presence in the cells does not alter protein functional activities. However, a review focusing particularly on the refolding and counteracting effects of the ILs against denatured proteins by multiple stresses is still missing. This perspective unveils the studies that have been conducted to improve protein stabilities with ILs as well as the refolding and counteracting abilities of these ILs against the denatured proteins under the influence of multiple stresses. We believe that ILs can provide significant environmental and economic advantages for biochemical processes in the near future. Essentially, numerous investigations are required to allow us to further explore the stabilizing properties of ILs over proteins.